2007
DOI: 10.1111/j.1462-5822.2006.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

The secreted autotransporter toxin, Sat, functions as a virulence factor in Afa/Dr diffusely adhering Escherichia coli by promoting lesions in tight junction of polarized epithelial cells

Abstract: SummaryAfa/Dr diffusely adhering Escherichia coli (DAEC) strains are responsible for urinary tract and intestinal infections. Both in intestine and kidney, the epithelial cells forming epithelium are sealed by junctional domains. We provide evidence that the Secreted autotransporter toxin, Sat, belonging to the subfamily of serine protease autotransporters of Enterobacteriaceae (SPATEs), acts as a virulence factor in Afa/Dr DAEC by promoting lesions in the tight junctions (TJs) of polarized epithelial Caco-2/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
103
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 86 publications
10
103
0
7
Order By: Relevance
“…77 The only documented secreted factor associated with DAEC infection is the SPATE Sat. Sat can induce rearrangement of the tight junction proteins ZO-1, ZO-3 and occludin increasing paracellular permeability but not transepithelial resistance 78 and can also bind spectrin, 79 rearrange focal adhesion associated proteins vinculin and paxillin, and cause cell detachment and caspase-independent cell death.…”
Section: Molecular Mechanisms Of Virulencementioning
confidence: 99%
“…77 The only documented secreted factor associated with DAEC infection is the SPATE Sat. Sat can induce rearrangement of the tight junction proteins ZO-1, ZO-3 and occludin increasing paracellular permeability but not transepithelial resistance 78 and can also bind spectrin, 79 rearrange focal adhesion associated proteins vinculin and paxillin, and cause cell detachment and caspase-independent cell death.…”
Section: Molecular Mechanisms Of Virulencementioning
confidence: 99%
“…In one study, afa, sfa and pap were detected among DAEC isolates from Bangui but none of them, nor DAEC as a whole, were associated with chronic diarrhea in HIV-positive patients [68]. Recently, Guignot et al have identified an autotransporter toxin, Sat, in UPEC and many diarrhea-associated DAEC [229]. Importantly, they showed that sat was significantly more commonly found in DAEC from children with diarrhea and UPEC than in DAEC from healthy children [229].…”
Section: Enteroaggregative E Colimentioning
confidence: 99%
“…Recently, Guignot et al have identified an autotransporter toxin, Sat, in UPEC and many diarrhea-associated DAEC [229]. Importantly, they showed that sat was significantly more commonly found in DAEC from children with diarrhea and UPEC than in DAEC from healthy children [229]. sat may represent a true DAEC virulence marker that future epidemiological studies, including those in Africa, may want to investigate.…”
Section: Enteroaggregative E Colimentioning
confidence: 99%
“…Having hemagglutinin and mucinolytic activity, Pic is able to penetrate the intestinal mucus cytoskeletal damage to tight junctions between intestinal epithelial cells. 64 Likewise, SigA, a SPATE largely associated with Shigella flexneri pathogenesis, is capable of inducing fodrin degradation causing catastrophic morphological changes in cells. 65 Interestingly, although only moderately prevalent in EAEC strains, SepA is the SPATE most strongly associated with severe diarrheal illness 63 though its role in EAEC pathogenesis remains largely uncharacterized.…”
mentioning
confidence: 99%